Free Tax Consultant Certification Exam (USKP) Fees on Tax Knowledge and Taxation Career Choice: Supporting SDG 4 - Dewi Kusuma Wardani; Suyanto Suyanto; Maristha Milesa Miftakhuljannah; Tyas Nur Pramesti; Sivantri Lado (Journal of Current Studies in SDGs, 2027)
Objective: The effect of tax knowledge on students’ interest in pursuing taxation careers and to analyze the moderating role of Free Tax Consultant Certification Exam (USKP) fees in the relationship between tax knowledge and taxation career choice. This study contributes to Sustainable Development Goal 4 (SDG 4: Quality Education) by emphasizing the importance of competency-based taxation education and professional development in higher education. Method: A quantitative research approach involving 105 accounting and taxation students from various universities in Indonesia. Data were collected through questionnaires and analyzed using simple regression analysis and Moderated Regression Analysis (MRA) with SPSS to examine the direct effect of tax knowledge and the moderating effect of USKP fees.  Results:  The results indicate that tax knowledge has a positive and significant effect on students’ interest in taxation careers. Furthermore, USKP fees significantly moderate the relationship between tax knowledge and taxation career choice, suggesting that certification accessibility influences students’ motivation to develop careers in taxation.  Novelty: To provide new insights by incorporating USKP certification fees as a moderating factor in taxation career decision-making. The findings highlight the importance of strengthening taxation education and improving access to professional certification as part of achieving SDG 4 through quality learning outcomes and professional competency development.